Islamic Education and the Formation of Student Muslim Identity in the Era of Globalization: A Systematic Literature Review - Hamzah, Andi Abdul; Jusoh, MD. Zamaakhsyari (Madania: Jurnal Kajian Keislaman, 2025)
Globalization poses significant challenges to students' religious identity through the influx of secularism and popular culture. This study aims to identify the role of Islamic education in shaping students' religious identity in the era of globalization. Employing a Systematic Literature Review (SLR) methodology, this research analyzes relevant literature related to Islamic education, Muslim identity, and globalization. The findings demonstrate that Islamic education can serve as a strategic instrument in strengthening students' religious identity through the internalization of robust moral and religious values. These findings also reveal the importance of adapting Islamic education curricula with approaches responsive to global challenges. This research addresses a gap in previous literature that has not comprehensively integrated the concepts of Islamic education, Muslim identity, and globalization challenges within a single analytical framework. The primary contribution of this study is the development of an adaptive Islamic educational approach model that maintains fundamental values in forming students' Muslim identity amid globalization currents. This research contributes both theoretically and practically by offering solutions to strengthen students' religious identity, while simultaneously providing opportunities for further research development and deeper exploration. Globalisasi membawa tantangan besar terhadap identitas keagamaan siswa melalui arus nilai-nilai sekularisme dan budaya populer. Penelitian ini bertujuan mengidentifikasi peran pendidikan Islam dalam membentuk identitas keagamaan siswa di era globalisasi. Menggunakan metode Systematic Literature Review (SLR), penelitian ini menganalisis literatur yang relevan terkait pendidikan Islam, identitas Muslim, dan globalisasi. Hasil penelitian menunjukkan bahwa pendidikan Islam mampu menjadi instrumen strategis dalam memperkuat identitas keagamaan siswa melalui internalisasi nilai-nilai moral dan agama yang kokoh. Temuan ini juga mengungkapkan pentingnya adaptasi kurikulum pendidikan Islam dengan pendekatan yang responsif terhadap tantangan global. Penelitian ini mengisi kesenjangan dalam literatur sebelumnya yang belum secara komprehensif mengintegrasikan konsep pendidikan Islam, identitas Muslim, dan tantangan globalisasi dalam satu kerangka analitis. Kontribusi utama penelitian ini adalah pengembangan model pendekatan pendidikan Islam yang adaptif namun tetap mempertahankan nilai-nilai fundamental dalam membentuk identitas Muslim siswa di tengah arus globalisasi. Penelitian ini berkontribusi secara teoritis dan praktis dalam menawarkan solusi untuk memperkuat identitas keagamaan siswa, sekaligus memberikan peluang pengembangan penelitian lebih lanjut untuk eksplorasi yang lebih mendalam.